2004
DOI: 10.2105/ajph.94.2.266
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated With Problem Use of Prescription Drugs

Abstract: We estimate the prevalence of and risk factors for the problem use of prescription drugs, overall and by therapeutic class. Applying logistic regression analysis to data from the National Household Survey on Drug Abuse, we found that nearly 1.3 million Americans aged 12 years and older experience problem use of prescription drugs signifying physiological dependence or heavy daily use. Those at greatest risk include older adults, females, those in poor/fair health, and daily alcohol drinkers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
97
1
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(115 citation statements)
references
References 18 publications
13
97
1
4
Order By: Relevance
“…For example, one recent study found that problem use of prescription drugs was significantly higher among daily alcohol drinkers (Simoni-Wastila and Strickler, 2004). In another study, college students who engaged in the nonmedical use of prescription stimulants were over six times more likely to report frequent binge drinking and over five times more likely to drive after binge drinking than college students who did not report nonmedical use of prescription stimulants (McCabe et al, 2005b).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, one recent study found that problem use of prescription drugs was significantly higher among daily alcohol drinkers (Simoni-Wastila and Strickler, 2004). In another study, college students who engaged in the nonmedical use of prescription stimulants were over six times more likely to report frequent binge drinking and over five times more likely to drive after binge drinking than college students who did not report nonmedical use of prescription stimulants (McCabe et al, 2005b).…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence documenting the association between alcohol use and NMUPD (Johansson et al, 2003;McCabe et al, 2005a,b;Simoni-Wastila and Strickler, 2004;Teter et al, 2003). For example, one recent study found that problem use of prescription drugs was significantly higher among daily alcohol drinkers (Simoni-Wastila and Strickler, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Women have been shown to be more likely than men to misuse prescription drugs (12,13). Some assert that women are more likely to misuse Rx drugs because they are more likely to be prescribed abusable forms of Rx drugs (14).…”
mentioning
confidence: 99%
“…Studije ukazuju na značajan udio mladih osoba koje na taj način razvijaju tzv. problematičnu uporabu droga, odnosno ovisničko ponašanje (Zacny i sur., 2003;Simoni-Wastila, Strickler, 2004).…”
Section: Razlozi Uporabe I Zlouporabe Lijekova Kod Mladihunclassified